1984
DOI: 10.2307/1939476
|View full text |Cite
|
Sign up to set email alerts
|

Interhabitat Differences in Energy Acquisition and Expenditure in a Lizard

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Ecological Society of America is collaborating with JSTOR to digitize, preserve and extend access to Ecology. Abstract. Cnemidophorus hyperythrus, a small (z4-g) teiid lizard,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

1985
1985
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(45 citation statements)
references
References 39 publications
2
42
0
1
Order By: Relevance
“…Maintenance of T b significantly higher than T a may reflect a behavioral mechanism for gaining heat (Verwaijen & Van Damme, 2007); P. bicolor probably use small sunlit patches in the leaf litter of the coffee shade plantation, as do gymnophthalmids in Amazonian rainforests (Vitt et al, 2003b). This ability to perform with such a low body temperature may reflect the highly abundant source of food, promoting a more passive foraging mode that allows them to be active during cloudy days and in cold microhabitats (Karasov & Anderson, 1984;Verwaijen & Van Damme, 2007). The significant relationships observed between T b , T a and T s suggest that microhabitats might be chosen at least partially on the basis of temperature; however, other factors may influence P. bicolor microhabitat preferences as stated above.…”
Section: Discussionmentioning
confidence: 99%
“…Maintenance of T b significantly higher than T a may reflect a behavioral mechanism for gaining heat (Verwaijen & Van Damme, 2007); P. bicolor probably use small sunlit patches in the leaf litter of the coffee shade plantation, as do gymnophthalmids in Amazonian rainforests (Vitt et al, 2003b). This ability to perform with such a low body temperature may reflect the highly abundant source of food, promoting a more passive foraging mode that allows them to be active during cloudy days and in cold microhabitats (Karasov & Anderson, 1984;Verwaijen & Van Damme, 2007). The significant relationships observed between T b , T a and T s suggest that microhabitats might be chosen at least partially on the basis of temperature; however, other factors may influence P. bicolor microhabitat preferences as stated above.…”
Section: Discussionmentioning
confidence: 99%
“…Increased activity from the 54% longer daily activity periods (Marler and Moore 1989) of the T-implanted males may also contribute to the 31% increase in energy expenditure. The teiid lizard Cnemidophorus hyperythrus is active 60% longer in woodland areas compared to scrub areas and has a corresponding 52% higher energy expenditure (Karasov and Anderson 1984). Estimates suggest that for lizards in the woodland areas, 83% of energetic costs is caused by increased activity and the remaining 17 % is caused by the higher body temperature during increased activity, suggesting that the increase in activity has a greater impact on the energy budget than changes in temperature.…”
Section: Discussionmentioning
confidence: 99%
“…There was no minimum adequate model because even when the two way interaction terms were omitted individually (wind speed × air temperature; wind speed × habitat; air temperature × habitat), to reveal just the main effects, the model was still insignificant (habitat: Stamps (1983) showed that vegetation structure played a critical role in reptile habitat selection for predator escape. Additionally, this vegetation cover has also been used for foraging (Karasov and Anderson, 1984), and mating (Diaz and Carrascal, 1991). Algyroides marchi is a lizard endemic to the mountainous region of south-east Iberian Peninsula.…”
Section: Habitat Variablesmentioning
confidence: 99%